DRILLS AND TRAINING ON BOARD SHIP IN MARITIME TRANSPORT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The advancement of technology has dramatically altered the maritime sector during the previous several decades. With the sector changing so dramatically, the tasks of sailors have also undergone a drastic shift. Containerization and flag-of-convenience shipping are two examples of notable developments. As a result of the intense rivalry amongst the affiliated enterprises, sailors' performance and rest have changed. Fewer people (mostly from other countries) are working, and the length of time spent at the port has been dramatically decreased. Because of this increase in shipbuilding, sailors must be prepared to work in a variety of hard positions on board a variety of ships. Seafarers must have specialized training in order to operate on certain kinds of ships, which in turn necessitates specialized skills. For sailors, training is a crucial element of their preparation. Pre-sea and post-sea training for sailors might be separated in this way. Simulators are essential for sailors' post-sea training once they've earned experience on board.